Comparative analysis of the humid and alkaline methods in the extraction of seed starch from Amaranthus quitensis L. - González García, Juan Carlos (2018)
In the present reserch, two methods for the extraction of starch from seeds of Amaranthus quitensis L. (Ataco) were analyzed in order to determine the procedure with the best performance and then to determine its main physical-chemical and functional characteristics. Initially, the inflorescences of the Ataco plants were collected, where their seeds are found, to later extract them, dry them to the environment and finally reduce them to fine dust. Then, simultaneous extractions of the starch contained in the flour were carried out by testing with two independent methods; the first wet method with bidistilled water and the second with an aqueous solution of sodium hydroxide (NaOH, 0.25 M); the starch extracted by both methods was washed and dried to the environment, to later calculate its yield, establishing that the highest yield is achieved with the method of extraction with NaOH solution. The results of the proximal analysis of the extracted products showed that there are significant differences (p≤ 0.05) in all properties analyzed since they vary depending on the method. Regarding the functional properties analyzed, it was found that as regards the Water Absorption Index (IAA) and the Water Solubility Index (ISA) there are significant differences between the values measured by each method. Regarding the temperature of gelatinization, there is no significant difference because this property does not depend on the extraction method of the starches but it varies depending on the plant.